Annual report on exchange arrangements and exchange restrictions. - International Monetary Fund.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
The material contains developments in the international exchange rate and restrictive systems.
oif 22/07/16, lje 22/07/16; opc 23/12/16
Loan
Keywords: Foreign exchange; Foreign exchange administration; Foreign exchange administration; Foreign exchange